ANALISIS PENGALAMAN PERJALANAN UMRAH TENTANG KEPUASAN JEMAAH UMRAH PENYANDANG DISABILITAS - Aji, Rizky Albar Pandu; Ferdinand, Novingky; Kumala, Destiana (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Performing Umrah is a profound spiritual aspiration for every Muslim, including individuals with disabilities. The journey to the holy land, which includes various rituals and worship activities, requires careful preparation, especially for those with special needs. This qualitative case study investigates the service strategies used by PT XYZ, Kebon Jeruk, a travel agency, to increase the satisfaction of Umrah pilgrims with disabilities. Data were collected through in-depth interviews with key personnel at PT XYZ and observation of their operational procedures. The findings show that PT XYZ's service strategy, which includes personal introduction to pilgrims with disabilities, specialized assistance, and comprehensive fulfillment of their unique needs, is highly effective. The provision of adequate facilities and thorough preparation ensure that Umrah trips for people with disabilities are conducted comfortably, safely, and with deep spiritual fulfillment. This effectiveness is further evidenced by prioritizing disabled pilgrims both during the preceding manasik (pilgrimage ritual training) in Indonesia and during the actual pilgrimage activities in the holy land